Friends and Supporters of the Democratic Task Force and Democratic Women's Agenda - Mildred Jeffrey::::::; Koryne Horbal:::::: (1976)
This June 1976 report from the Democratic Task Force and Democratic Women's Agenda updates supporters on the status of women's issues in the Democratic Party Platform and Rules Committee. It states that most goals of the Democratic Women's Agenda were successfully incorporated into the platform, including opposition to a constitutional amendment banning abortion, though this required significant advocacy. However, a stronger resolution mandating equal division of male and female delegates at future conventions was defeated in the Rules Committee and replaced by a weaker measure leaving implementation to state parties. A minority report was filed to allow debate on equal representation at the convention, and supporters are urged to assess delegate sentiment and assist the effort. The document also notes passage of a Charter amendment strengthening affirmative action and provides logistical details for Women's Caucus meetings and events at the convention.